2022
DOI: 10.3390/app12157870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freeze-Thaw Damage on the Physical, Mechanical, and Acoustic Behavior of Sandstone in Urumqi

Abstract: The Urumqi area in China is a seasonally cold region, and the rock structures in the region are susceptible to freeze-thaw (F-T) weathering. Therefore, this study investigated the effect of F-T on the physical, mechanical, and fracture behavior of sandstone from Urumqi. The acoustic emission method (AE) was used to determine the stress thresholds for the initiation and development of cracks in the samples under cyclic F-T action. The results suggested that parameters such as P-wave velocity, elastic modulus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The raw acoustic emission waveforms can be analyzed for various parameters, such as the peak counts, energy, and entropy, to determine the fracture initiation point and identify the damage stage [25]. Xu et al [26] found a specific relationship between the acoustic emission signal and the stress-strain behavior of the material during loading. Therefore, in this study, the changes in the stress threshold of CGB during their damage process after chemical erosion were explored with acoustic emission technology, and the changes in the acoustic emission signals of the CGB samples with different erosion times were analyzed and evaluated.…”
Section: Effects On the Ae And Failure Behaviormentioning
confidence: 99%
“…The raw acoustic emission waveforms can be analyzed for various parameters, such as the peak counts, energy, and entropy, to determine the fracture initiation point and identify the damage stage [25]. Xu et al [26] found a specific relationship between the acoustic emission signal and the stress-strain behavior of the material during loading. Therefore, in this study, the changes in the stress threshold of CGB during their damage process after chemical erosion were explored with acoustic emission technology, and the changes in the acoustic emission signals of the CGB samples with different erosion times were analyzed and evaluated.…”
Section: Effects On the Ae And Failure Behaviormentioning
confidence: 99%
“…Zhang et al [2] reported that the deterioration degree of granite increases as the temperature increases, and the cooling methods also have effects on the physical properties of the rock. Xu et al [3] suggested that as freeze-thaw damage increases, the mechanical parameters (elastic modulus and peak stress) decrease, while the porosity increases. Zhou et al [4] developed electro-hydraulic servo-point load equipment and investigated the influence of the loading rate on the axial stress distribution of rock.…”
Section: Mechanical Properties Of Rocks Under Different Conditionsmentioning
confidence: 99%